2022
DOI: 10.36401/jipo-22-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting KRAS: Crossroads of Signaling and Immune Inhibition

Abstract: Mutations of RAS are commonly seen in human cancers, especially in lung, colorectal, and pancreatic adenocarcinoma. Despite huge effort for decades, targeting RAS mutations has been “undruggable” because of the molecular instability of RAS protein inhibition. However, the recent discovery of the KRAS G12C inhibitor paved the way to expand therapeutic options for patients with cancer harboring the KRAS G12C mutation. At the same time, the successful development of immune checkpoint inhibitors (ICIs) drastically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…This study highlighted the potential for combining immunotherapy with KRAS inhibitors in KRAS -mutated BTCs. The results showed that GBC had a relative higher mean and median TMB and proportion of PD-L1 high expression, which are favorable factors for ICI therapy response in KRAS -mutated GBC . In a 2023 study by Jeong et al, patients with KRAS allelic variants and PD-L1 positivity had a longer progression-free survival than patients with KRAS allelic variants and PD-L1 negativity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study highlighted the potential for combining immunotherapy with KRAS inhibitors in KRAS -mutated BTCs. The results showed that GBC had a relative higher mean and median TMB and proportion of PD-L1 high expression, which are favorable factors for ICI therapy response in KRAS -mutated GBC . In a 2023 study by Jeong et al, patients with KRAS allelic variants and PD-L1 positivity had a longer progression-free survival than patients with KRAS allelic variants and PD-L1 negativity.…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that GBC had a relative higher mean and median TMB and proportion of PD-L1 high expression, which are favorable factors for ICI therapy response in KRAS -mutated GBC. 42 In a 2023 study by Jeong et al, 43 patients with KRAS allelic variants and PD-L1 positivity had a longer progression-free survival than patients with KRAS allelic variants and PD-L1 negativity. Preclinically, KRAS inhibitors have been associated with promotion of a proinflammatory tumor microenvironment, increased major histocompatibility complex class I protein expression, and synergies with immunotherapy to enhance antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to ICIs that block PD-1/PD-L1 may be highly dependent on concurrent mutations 178 . According to several studies, although ICIs can effectively treat patients with gastrointestinal cancers or NSCLC harboring a KRAS mutation, primary or acquired resistance to ICIs may occur 179 . Targeted next-generation sequencing of lung adenocarcinoma revealed that KRAS mutation with TP53 and MET mutations is strongly linked to increased PD-L1 expression 180 .…”
Section: Treatments Targeting Kras and The Tmementioning
confidence: 99%
“…This group of genes is involved in the control of cell growth, survival, differentiation and potentially shaping the local tumour-immune microenvironment [9,10], and is frequently associated with genomic alterations in human cancers. KRAS is the most commonly mu-tated RAS isoform, making up approximately 85% of oncogenic RAS mutations in all cancer types [11]. KRAS mutations are seen in 61-86% of pancreatic ductal adenocarcinomas, 33-52% of colorectal adenocarcinomas, and 17-32% of lung adenocarcinomas.…”
Section: Kras Mutations: Biology and Signaling Pathwaysmentioning
confidence: 99%